(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The electrochemical methods used to determine the antioxidant properties and total phenolic content in wine are presented in this review paper like voltammetry, potentiometry, mass spectrometry, chromatography, and electrochemical sensor. To detect and measure the antioxidant activity of wine developed many analytical methods to present an easy, fast response and inexpensive systematic approach used in the field. Electrochemical sensors are the best tools for antioxidant properties determination in the research field. The electrochemical sensor has elevated sensitivity, simplicity, fast response time, and best efficiency. These sensors are used for different purposes with a limited ability to emphasize the advantages and distinguish between them. Quantification of specific antioxidants or total antioxidant content using electrochemical sensors has been analyzed. This summary proves the reliability of the electrochemical sensor.